2016
DOI: 10.1002/slct.201600771
|View full text |Cite
|
Sign up to set email alerts
|

Towards Iron-Catalyzed Sonogashira Cross-Coupling Reactions

Abstract: Herein we report on the selective iron‐catalyzed cross‐coupling reaction of terminal phenylacetylenes with iodo‐aryl derivatives to afford the respective coupling products in the presence of 10 mol% FeCl2(bdmd) and 10 mol% [Cu(CH3CN)4]BF4 (bdmd=bis((diphenylphosphanyl)methyl)diphenylsilane). The yields are moderate to good in 1,4‐dioxane or DMF. This is the first example of a well‐defined and fully analysed ferrous complex acting as a precatalyst in Sonogashira cross‐coupling reactions. Notably, FeCl2(bdmd) is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 38 publications
0
5
0
Order By: Relevance
“…Apfel et al reported the first selective cross-coupling reaction between terminal phenylacetylene and iodobenzene derivatives using Fe(II) bisphosphine complexes, which serve as precatalyst (Scheme 17) [33]. In the reaction ortho-iodo derivatives Scheme 18: Synthesis of 7-azaindoles using Fe(acac) 3 as catalyst.…”
Section: Non-green Protocolsmentioning
confidence: 99%
See 1 more Smart Citation
“…Apfel et al reported the first selective cross-coupling reaction between terminal phenylacetylene and iodobenzene derivatives using Fe(II) bisphosphine complexes, which serve as precatalyst (Scheme 17) [33]. In the reaction ortho-iodo derivatives Scheme 18: Synthesis of 7-azaindoles using Fe(acac) 3 as catalyst.…”
Section: Non-green Protocolsmentioning
confidence: 99%
“…Apfel et al reported the first selective cross-coupling reaction between terminal phenylacetylene and iodobenzene derivatives using Fe(II) bisphosphine complexes, which serve as precatalyst ( Scheme 17 ) [ 33 ]. In the reaction ortho -iodo derivatives with an amino or alcohol functionality showed higher yields than the corresponding iodo derivatives with same substitutions in meta and para position due to the ortho directing effect.…”
Section: Reviewmentioning
confidence: 99%
“…Furthermore, DFT calculations revealed a mixed SOMO of 3d z 2 and 3d x 2 -y 2 character which is highly dependent on the complex geometry. 230 In another example, Apfel et al, 230,231 showed that Ni and Fe complexes bearing the Triphos(2-((diphenylphosphaneyl)methyl)-2-methylpropane-1,3-diyl)bis(diphenylphosphane) and TriphosSi(((methylsilanetriyl)tris-(methylene))-tris(diphenylphosphane)) ligands are potential noble metal-free alternatives for the C-C cross-coupling of aryl iodides and alkynes. 231,232 Owing to the high steric hindrance of the Triphos ligand, such Ni complexes did not show any disproportionation of the respective Ni 11 complexes to Ni 0 and Ni 21 , and also no evidence of any dimerisation to form the di-nickel complex.…”
Section: C-c Cross-couplingmentioning
confidence: 99%
“…230 In another example, Apfel et al, 230,231 showed that Ni and Fe complexes bearing the Triphos(2-((diphenylphosphaneyl)methyl)-2-methylpropane-1,3-diyl)bis(diphenylphosphane) and TriphosSi(((methylsilanetriyl)tris-(methylene))-tris(diphenylphosphane)) ligands are potential noble metal-free alternatives for the C-C cross-coupling of aryl iodides and alkynes. 231,232 Owing to the high steric hindrance of the Triphos ligand, such Ni complexes did not show any disproportionation of the respective Ni 11 complexes to Ni 0 and Ni 21 , and also no evidence of any dimerisation to form the di-nickel complex. The Kumada cross-coupling abilities of these complexes were also studied by Apfel et al 223 The precatalyst is based on the EPR silent Ni 21 complex, which reverts to Ni 11 following addition of a Grignard reagent to the solution.…”
Section: C-c Cross-couplingmentioning
confidence: 99%
“…However, similar yields were obtained when the respective Ni(II) complex was utilized for the very same reaction. We recently showed that Triphos (2-((diphenylphosphaneyl)methyl)-2-methylpropane-1,3-diyl)bis (diphenylphosphane)-and Triphos Si (((methylsilanetriyl)tris(methylene))-tris(diphenylphosphane))-derived Ni and Fe complexes are potential noble metal-free platforms to conduct the C-C crosscoupling of aryl iodides and alkynes [23,24]. Furthermore, the Ni(Triphos) complexes were shown to stabilize various oxidation states of Ni (Scheme 2) [25].…”
Section: Introductionmentioning
confidence: 99%